(SXF[PLMA FUDA YSREROJV(B: (SMAXAVMFYFV VXJP FSLZAPFLA XRY BUA[RY(B, (SYSRDFLFV MAXAVMFYFV(B, (SZUADOAXAs - (SOga(Sugac(Smrw [ujvxrw Ps ((SAyxrfmervj(B,s, 1997)
(SJ VYPAUORDJ XRY BUA[RY MULXJULA AVXR[LAV XRY AVYPF[RYV BUA[RY J FYVXAKFLA X]P MAXAVMFY]P SAUAOFXURL V[FELAVORY X]P KFOFNL]VF]P BUA[]EJ SUAPJs
(SJ VYPAUORDJ XRY BUA[RY MULXJULA AVXR[LAV XRY AVYPF[RYV BUA[RY J FYVXAKFLA X]P MAXAVMFY]P SAUAOFXURL V[FELAVORY X]P KFOFNL]VF]P BUA[]EJ SUAPJs